Estudo dos receptores de estrogênio e progesterona e da espessura da mucosa no epitélio vaginal em mulheres menopausadas portadoras de síndrome genito-urinária submetidas à terapia por laser de CO2 fracionado - Pinho, Stella Catunda [UNIFESP] (2020)
Objective: To analyze the effectiveness of Fractional CO2 Laser (Monalisa Touch ®) and compare it with the use of topical estriol in terms of the quantity and distribution of estrogen and progesterone receptors in the vaginal epithelium and the probable relationship of the thickness of this epithelium in patients with postmenopausal genitourinary syndrome. Method: a total of 25 women with menopausal genitourinary syndrome met the inclusion criteria, a biopsy of the vaginal epithelium was performed with analysis of thickness and initial and final immunohistochemistry. Results: Regarding the estrogen receptor, we found that the levels of this receptor were statistically the same between groups, both at the beginning (p = 0.769) and at the end (p = 0.586) and there was no change over time in the group. estrogen (p = 0.207), but in the laser an increase in the level of this receptor was confirmed (p = 0.004). However, changes in estrogen receptor levels showed no association with treatment (p = 0.238). In the analyzes of the progesterone receptor, we noticed that the levels were statistically the same between the groups, both at the beginning (p = 0.124) and at the end (p> 0.999) and that there was no change over time in both groups: estrogen (p = 0.157) and laser (p = 0.564). These changes in the levels of the progesterone receptor showed no association with the type of treatment (p> 0.999). The correlation between vaginal epithelial thickness and levels of estrogen and progesterone receptors was investigated. For this, the Spearman correlation coefficient (S) was estimated, which quantifies the tendency of growth or decrease between quantitative data and it was found that it was not possible to evidence a significant correlation between epithelium thickness and levels of estrogen and progesterone receptors. Conclusion: It was possible to observe through immunohistochemical analysis that there was an increase in the number of estrogen receptors and maintenance of the amount of progesterone receptors in the vaginal epithelium in both groups, with no statistical difference between them. Another important conclusion is that there was no statistically significant relationship between the thickness and density of these receptors. This research has shown that it is possible to obtain good results with laser therapy which, although more expensive and less accessible so far, has results similar to the gold standard and does not bring the drawbacks of the side effects of hormone therapy.